Sobre lágrimas, corpos e silêncios pedagógicos : transitando entre educação física escolar, sexualidades e gênero - Alves e Silva, Marco Aurélio (Educación Física y Ciencia.)
This text talks about the objectification of the 'gay body' as different in the school context from bodily experiences lived in the early grades of Elementary School, during Physical Education (PE) classes, from a private school in Goiás. The narrative of the one who experienced it, the reading of the regulatory documents of Primary Schools in Brazil and surveying homophobic pedagogical practices aim to show how corporeality is a collective learning. In this way, the violence practiced by the head teacher, the PE teacher and the students to contain and control the 'different one' is the very condition of existence. Therefore, we understand that the production of what is 'different' in school is a form of knowledge and that the fact of not having gender and sexuality subjects in the curriculum, under the justification it belongs to the private-family sphere, does not exempt schools from this responsibility. That is, when teaching what is not recognized as knowledge, it does not assume the pedagogical responsibility that it refutes and ignores. We believe, therefore, that the visibility of emerging corporealities does not necessarily make them more understandable and that an expanded pedagogical practice, committed to human rights, can enable new experiments of existence, of living lives.